A Note on a Covariance Matrix with Its Application to the Two-Parameter Hypothesis on Risky-Asset Choice - Ichishi, T. (Review of Economic Studies, 1969)
Journal Article A Note on a Covariance Matrix with its Application to the Two-Parameter Hypothesis on Risky-Asset Choice Get access T. Ichiishi T. Ichiishi Keio University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 2, April 1969, Pages 254–256, https://doi.org/10.2307/2296842 Published: 01 April 1969 Article history Received: 29 February 1968 Revision received: 31 October 1968 Published: 01 April 1969